Identificación de parte de la decoración de la pajcha colonial 7572, del Museo de América (Madrid) - Ramos Gómez, Luis (Revista Española de Antropología Americana, 2003)
We reconstruct here part of the decoration of a pajcha from XVIIIth century located at «Museo de América» (Madrid); his recreation was possible thanks to the discover of a quero at the Inka Museum in Cuzco, wich it is represented a scene of a farmer working the land with oxes and plough. The rest of the decoration shows different elements related with this scene and, as an heraldic element, an allegory of ‘The Inca’s Epoch’.
Keywords: Pajcha; Peru; XVIIIt; Century; Country; Scene; Heraldic; Element